The interactions between plasma membrane depolarization and glutamate receptor activation in the regulation of cytoplasmic free calcium in cultured cerebellar granule cells - Courtney, MJ (J Neurosci, 1990)
The complex modulation of cytoplasmic free calcium concentration ([Ca2+]c) in primary cultures of cerebellar granule cells in response to glutamate receptor agonists has been the subject of several contradictory reports. We here show that 3 components of the [Ca2+]c response can be distinguished: (1) Ca2+ entry through voltage-dependent Ca2+ channels, following KCl- or receptor-evoked depolarization, (2) Ca2+ entry through NMDA receptor channels, and (3) liberation of internal Ca2+ via a metabolotropic receptor. Depolarization with KCl induced a transient [Ca2+]c response (subject to voltage inactivation) decaying to a sustained plateau (largely inhibited by nifedipine). The NMDA response was potentiated by glycine, totally inhibited by (+)5- methyl-10,11-dihydro-5H-dibenzo[a,d]cyclohepten-5,10-imine maleate (MK- 801), and blocked by Mg2+ in a voltage-sensitive manner. Polarized cells displayed small responses to quisqualate (QA) and alpha-amino-3- hydroxy-5-methyl-4-isoxazole-propionic acid (AMPA). Depolarization enhanced a transient response to QA, but not to AMPA. Trans-1-amino-1,3- cyclopentanedicarboxylic acid (trans-ACPD), a selective agonist for the metabolotropic glutamate receptor, caused a transient elevation of [Ca2+]c, which was blocked by prior exposure to QA but not AMPA. The prolonged [Ca2+]c response to kainate (KA) can be resolved into 2 major components: an indirect NMDA receptor-mediated response due to released glutamate and a nifedipine-sensitive component consistent with depolarization-mediated entry via Ca2+ channels. 6-Cyano-7- nitroquinoxaline-2,3-dione (CNQX), QA at greater than 10 microM, and AMPA (but not trans-ACPD) reversed the KA response, consistent with an inactivation of the KA receptor.(ABSTRACT TRUNCATED AT 250 WORDS)